Political science in the Federal Republic of Germany – featured examples - Bielawska, Agnieszka; Wiśniewski, Janusz (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2016)
This paper presents the history of German political science and its current status. It contains a comparison of modern Political Science majors offered by the three top rated universities in German rankings – the University of Potsdam, Free University of Berlin and Humboldt University. It outlines the structure of political science studies, the type of courses offered and the literature used during teaching.

Niniejszy artykuł zarysowuje historię niemieckiej nauki o polityce i jej stan obecny. Zawiera porównanie współczesnych kierunków politologicznych oferowanych przez trzy najlepiej oceniane w niemieckich rankingach uniwersytety – Uniwersytet Poczdamski, Wolny Uniwersytet Berliński i Uniwersytet Humboldta w Berlinie. Przedstawia strukturę studiów politologicznych, rodzaj oferowanych kursów oraz literaturę wykorzystywaną podczas nauczania.
Politologia w Republice Federalnej Niemiec – wybrane przykłady
Keywords: political science; science; university; Germany; politologia; nauka; uniwersytet; RFN